A New Case of de novo Variant c.892C>T (p.Arg298Trp) in NACC1: A First Case Report From China - Lyu, Baiyu; Dong, Yan; Kang, Juan (Frontiers in Pediatrics, 2021)
Background: The nucleus accumbens associated 1 (NACC1) gene is a transcription factor member of the BTB/POZ family. A de novo heterozygous c.892C>T (p.Arg298Trp) variant in the NACC1 may define a syndrome characterized by intellectual disability, infantile epilepsy, congenital cataract, and feeding difficulties. Case Presentation: We report a new case with a neurodevelopmental disorder characterized by severe intellectual disability, infantile epilepsy, congenital cataract, and feeding difficulties. Brain MRI reveals brain dysplasia. We observe a de novo heterozygous c.892C>T (p.Arg298Trp) variant in the NACC1 gene in this case. Now, the child regularly goes to the hospital for rehabilitation training (once a month). Sodium Valproate (10 mg/kg/day) and Clobazam (10 mg/kg/day) are used in the treatment of epilepsy. A total of three articles were screened, and two papers were excluded. The search revealed one article related to a syndrome caused by a de novo heterozygous c.892C>T (p.Arg298Trp) variant in the NACC1; they screened the main clinical features of eight cases of a syndrome, which were summarized and analyzed. Conclusions: The NACC1 gene is a member of the BTB/POZ family of transcription factors. A de novo heterozygous c.892C>T (p.Arg298Trp) variant in the NACC1 may define a syndrome characterized by intellectual disability, infantile epilepsy, congenital cataract, and feeding difficulties. At present, there is no effective cure. In the future, we need more cases to determine the phenotype–genotype correlation of NACC1 variants. Many questions remain to be answered, and many challenges remain to be faced. Future transcriptional studies may further clarify this rare, recurrent variant, and could potentially lead to targeted therapies.